Carbonate‐Associated Phosphate (CAP) Indicates Elevated Phosphate Availability in Neoarchean Shallow Marine Environments. Issue 6 (14th March 2022) - Ingalls, M.; Grotzinger, J. P.; Present, T.; Rasmussen, B.; Fischer, W. W.
Abstract: Phosphorus is essential for cell biology, yet scarce in modern marine environments wherein free phosphate is consumed by life or titrated by calcium to form apatite minerals. The environmental conditions under which the early biosphere emerged and phosphorus was integrated throughout biochemistry is yet unknown. We measured the phosphate concentrations of 2.8–2.5 Ga shallow marine carbonate facies across six Neoarchean shelf‐ramp environments. We found that the P/Ca ratios of Neoarchean stromatolites, micrites, and crystal fans were >4‐fold to 12‐fold more enriched in carbonate‐associated phosphate than modern marine coral skeletons and abiotic Phanerozoic carbonates. Our results support the view that Archean productivity was limited by the availability of electrons rather than phosphate or other nutrients, and help explain why phosphorus is so central to the molecules, metabolisms, and bioenergetics observed in cells. Plain Language Summary: Phosphorus is an essential element for life processes. Today, phosphorus is negligible in the surface oceans and exists in very low concentrations in the deep oceans, and thus is the primary limitation on net primary productivity. This circumstance sets up the paradox of why phosphorus plays a key role in the structures and processes of cell biology. Were phosphorus concentrations higher in the Archean oceans early in the evolutionary history of cell biology? In this work, we compared phosphate concentrations in shallow marine carbonates from the Neoarchean (2.8–2.5 billion years ago) and the Phanerozoic (<550 million years ago). We found that primary carbonate structures and fabrics from the Neoarchean yielded significantly higher phosphate concentrations than in the Phanerozoic, and interpreted this to mean that Archean seawater was more enriched in phosphorus than modern oceans. Key Points: P/Ca is higher in Neoarchean shallow marine carbonates than Phanerozoic and modern shallow marine carbonates Higher phosphate concentrations in Neoarchean than modern seawater indicates that early marine life was not phosphate‐limited